5 GHz Wi-Fi Information and Analyzer Android Application - Tajol Akman, Muhammad Uzair; Bahari, Azlina (Progress in Engineering Application and Technology, 2023)
This paper presents the design and implementation of an Android application that acts as an information and analyzer tool for 5 GHz Wi-Fi networks. The rapid development and widespread use of mobile devices have led to an increasing demand for reliable and high-speed wireless networks. One of the most popular wireless network standards is Wi-Fi, which operates in the 2.4 GHz and 5 GHz frequency bands. The 5 GHz band is considered to be less congested and therefore offers better performance, making it a preferred choice for high-bandwidth applications such as streaming and gaming. However, selecting the best channel for a 5 GHz Wi-Fi network can be challenging, especially in environments with a large number of other Wi-Fi networks.